Structural integrity assessment of cracked composite plate under aeroelastic loading by means of XFEM - Abdullah, Nur Azam; Curiel-Sosa, J.L.; Wirawan, Nanda; Akbar, Mahesa (2018)
In this paper, a novel procedure to analyse dynamic crack under aeroelastic loading by means of XFEM and Doublet Lattice Method (DLM) - FEM coupling is presented. The present work performed a new investigation on the crack propagation on the composite plate exerted by the unsteady aerodynamic loading during the cruise speed. The study on whether the failure due to instability, i.e., flutter, comes first or the crack propagates first until the structural failure is focused. The flutter speed is determined, and the maximum cruise speed is assessed based on the regulation guided by the FAR 23. The proposed method is used to solve the limitation in XFEM within Abaqus that only general static and implicit dynamic analysis can be performed. As the propagation of crack should be analyzed, the composite plate is assigned based on the energy release rate (ERR) of that type of material. The influence of a crack growth on a composite plate at cruise speed is shown in some details. Despite the fact that the crack is propagated at this speed, with initial crack ratio of 0.25, the crack has just grown slightly.